Effect of 0.1% diclofenac ophthalmic solution on inflammatory response and macular thickness following phacoemulsification cataract surgery - Zielińska, Edyta; Rokicki, Dariusz; Wielgórski, Mariusz; Szaflik, Jerzy; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Purpose : To evaluate 0.1% diclofenac sodium as an adjunctive therapy with loteprednol etabonate on postoperative inflammation in the anterior chamber and on foveal and parafoveal retinal thickness. Material and methods : Eighty eyes eligible for phacoemulsification were enrolled in a randomized clinical trial. Patients in group I (N = 40) received anti-inflammatory treatment consisting of 0.1% diclofenac with 0.5% loteprednol; group II (N = 40) patients received 0.5% loteprednol alone. Best corrected visual acuity and intraocular pressure were measured, and laser flarephotometry was done. Foveal and parafoveal thickness were assessed by optical coherence tomography. Results : Median flare values decreased more rapidly in group I at 7 and 14 days (7.9 and 7.4 ph/ms, respectively) than in group II (13.7 and 11.8 ph/ms, respectively; p < 0.0001). Group II had significantly increased parafoveal thickness at 14 and 42 days (median 285.59 μm, p = 0.001 and 288.38 μm, p < 0.001, respectively). Parafoveal thickness differed significantly between groups at 14 and 42 days (p = 0.0085, p = 0.0004, respectively). Conclusions : Eyes treated with both diclofenac sodium and loteprednol etabonate showed less inflammatory response and were less likely to develop foveal and parafoveal thickening than those treated with steroid only.